A Viability Analysis of Tumor-Bearing Frozen Autograft for the Reconstruction After Resection of Malignant Bone Tumors Using 99mTc-MDP Scintigraphy. (14th January 2023) - Araki, Yoshihiro; Yamamoto, Norio; Hayashi, Katsuhiro; Takeuchi, Akihiko; Miwa, Shinji; Igarashi, Kentaro; Higuchi, Takashi; Abe, Kensaku; Taniguchi, Yuta; Yonezawa, Hirotaka; Morinaga, Sei; Asano, Yohei; et al.
Abstract : Purpose of the Report: Several methods are used to reconstruct bony defects after malignant tumor excision. Tumor-bearing frozen autograft reconstruction is a biological procedure in which tumor-bearing bone is reused after devitalization with liquid nitrogen to kill tumor cells. The viability of frozen autografts has not been fully evaluated over time. We therefore aimed to evaluate the viability of devitalized bone grafts, using 99m Tc-MDP scintigraphy. Patients and Methods: Seventy-four patients who underwent frozen autograft reconstruction after the excision of a malignant bone tumor were enrolled. Two hundred forty-two postoperative 99m Tc-MDP scans were reviewed. For a quantitative analysis, the region of interest on the frozen bone segment and a symmetric region of interest on the contralateral normal area were manually set. The radioactive tracer uptake ratio was calculated by dividing the count density of the frozen bone segment by that of the contralateral normal area in each image. An uptake ratio of 0.9 to 1.1 was defined as a normalization of tracer uptake. Results: Normalization of tracer uptake was achieved in 95% to 97% of the cases by 60 months postoperatively, and earlier in the middle zone and peripheral zone in the pedicle freezing group in comparison to the free freezing group (both P = 0.03). Fracture and nonunion was associated with a low uptake ratio, whereas infection was associated with a high uptake ratio before the occurrence of the event. Conclusions: The calculation of the uptake ratio using 99m Tc-MDP scans was an objective and accurate evaluation method. The period to normalization of tracer uptake in the pedicle frozen bone was significantly earlier than that in the free frozen bone. The postoperative complications can be also predicted.